The effect of social media usage on millennials’ political knowledge and political participation in the presidential election in Indonesia: A structural equation modelling analysis - Ais Shafiyah Asfar; Rachmah Ida; Aribowo (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2025)
In democratic countries such as Indonesia, social media has gained importance as one of the tools to improve political literacy that leads to increase in political participation. This phenomenon has prompted many studies to explore the impact of technology-based communication tools on political knowledge and political participation. This article aims to determine the significance effect of social media usage on political knowledge and political participation in a structural model as well as to investigate whether social media usage effects political participation directly or through the mediating role of political knowledge. This study uses two theoretical frameworks, namely Uses and Gratification Theory and Cognitive-Affective-Conative Framework. The location of this research is in Surabaya, Indonesia with 400 respondents were taken by using multi-stage random sampling technique that represent the population of eligible voters in Surabaya. The research results show that the structural model built confirms the hypothesized theoretical model. The conclusion of this study shows that social media usage has directly and indirectly influences political participation in the presidential election in Indonesia.